Wild edible plants used as food source by the Melanau community in Balingian, Mukah - Zahora, Ismail; Mugunthan, Perumal; Patricia King, Jie Hung; Fauziah, Abu Bakar; Adam Harris Gerten Ritay, Abdullah; Maznah, Muning (2022)
Food is a basic need that can be met by a variety of sources, one of which is plant-based. Most tribal communities meet their food needs by using various plant parts that are nutritious in nature. Plant resources gathered from the wild are important sources of livelihood. This study was conducted to study the wild edible plants consumed by the Melanau community in Balingian district as a source of food for daily living. A face-to-face interview involving 40 respondents was conducted to acquire information on demographics, plants used as food, and part of use. Other uses of plants were also recorded. 20 wild plants had been found to be used for food consumption. Ten species were chosen for this study that is widely or often used by the Melanau community as a food source (Premna serratifolia, Etlingera coccinea, Nypa fruticans, Nephrolepis bisserata, Eleiodoxa conferta, Sonneratia sp., Stenochlaena palustris, Pentaspadon motleyi, Shorea macrophylla, and Pangium edule). The social values held by the community have a significant bearing on the manner in which wild edible plants are consumed and conserved by the community for food needs. This study highlighted the significance of wild plant species as a food source for the Melanau community in Balingian. Yet, due to the growing population, over-exploitation and depletion, and the threat of extinction to biodiversity by natural and artificial hazards, there is a need to collect and conserve those species. Multiplication of its population through advanced techniques can be tried and introduced in ecologically rich areas and botanical gardens to increase the accessibility of the species.